Cinética de cristalização não isotérmica de compósitos de biopoliamidas com argila organofilizada cloisite 30b - Menezes, Amanda da Silva Viana (2022)
During the solidification of semi-crystalline polymers, the presence of impurities affects their crystallization behavior. The behavior of crystallization in polymers can be studied by kinetic means of isothermal crystallization or non-isothermal crystallization. In this context, the present work aims to evaluate the influence of the nanoload on the morphology of three composites using the following matrices: PA 6.10, PA 10.10 and PA6.10/PA10.10, with the same percentage of clay concentrations, 0%, 3 %, 5% and 8%, as well as to evaluate the influence of the addition of CLOISITE 30B montmorillonite clay nanoload on the crystallization kinetics of the referred composites. For this, samples of polyamides and their composites with and without the addition of CLOISITE® 30B clay, at different concentrations, were processed by extrusion and injection. The characterization of the samples was initially performed by XRD AND SEM, to evaluate possible intercalation/exfoliation of clay in polyamides and composites. The results showed the presence of exfoliated structures at low clay concentrations and intercalated structures with increasing nanoload content. Through thermal characterization by DSC analysis and making use of the Jeziorny model, for non-isothermal crystallization kinetics, it was found to be adequate to describe the behavior of crystallization kinetics in all materials under study and, the fractional values obtained for n are typical of non-linear growth rates, resulting from heterogeneous nucleation and/or different crystal growth regimes.